MicroRNA 31 in activating granulocytes through regulation of fork head box protein P3 gene in hepatitis C virus related liver disease - Noha A. Amin; Rady E. El-Araby; Ayat S.M. Hassan; Khaled M. Ragab; Manal Y. Zahran; Ola B. Aboelnil (Journal of the Arab Society for Medical Research)
Background/aim The role of microRNA 31 (miRNA-31) role and fork head box protein P3 (FOXP3) protein in pathogenesis of chronic liver diseases as well as hepatocellular carcinoma (HCC) is complex. However, the expression levels or functions alterations of miRNA-31and FOXP3 could affect hepatitis C virus (HCV) infection outcome. FOXP3 and miRNA-31 have emerged as pivotal molecules influencing immune tolerance, fibrosis, and tumor progression in this context. Moreover, miRNA-31 may also regulate the immunological response of the granulocytes, primarily neutrophils. The present work aims to evaluate the possible effect of miRNA-31 in activating granulocytes through the regulation of the FOXP3 gene in HCV related liver disease. Patients and method This case–control study included 60 patients with persistent HCV infection divided into three groups (20 each) as follows: HCV infection patients’ group, HCV infection patients with cirrhosis group, and HCV infections patients with HCC group. In addition to 20 healthy patients served as a control group. Bioinformatics were used to select FOXP3 gene and its relations. miRNA-31 and FOXP3 gene expression were quantified using real-time PCR. Activated granulocyte percentage expressing CD16 was done by flow cytometry. Results After Bioinformatics selection of FOXP3 and its relation to miRNA-31, the present results disclosed that miRNA-31 was significantly upregulated (P<0.05) in both HCV with liver cirrhosis and without liver cirrhosis and in HCC groups in comparison with the control group. The expression of the FOXP3 gene was significantly downregulated (P<0.05) in both HCV with liver cirrhosis and without liver cirrhosis, whereas it was significantly upregulated (P<0.05) in the HCC group in comparison with the control group. Moreover, FOXP3 expression was significantly upregulated (P<0.05) in the HCV with cirrhosis and HCC groups when compared with HCV group without cirrhosis. In addition, there was a significant increase (P<0.05) in granulocyte CD16+ percentage in the HCV with cirrhosis and HCC groups, in comparing with HCV without cirrhosis group. Conclusion This work concluded that the miRNA-31 has a role in activating granulocytes (CD16+) through the regulation of FOXP3 gene in HCV with or without liver cirrhosis. Moreover, miRNA-31 and FOXP3 gene could be used as new biomarkers in HCV-induced liver cirrhosis and HCC.